Development of Automatic Sprinklers and Monitoring of Red Chilli Cultivation Based on the Internet of Things (IoT) - Walid , Miftahul; Burhan , Sohibul (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2023)
Current technology has significantly impacted various sectors of life, including education, government offices, and agriculture. The use of information technology aims to simplify and bring efficiency to various aspects. In this era of globalization, technology plays a crucial role for Indonesia, a country that lags behind in technological advancements, especially in the field of agriculture. Clear innovation is needed for this nation to compete on the international stage. The presence of technology that helps improve human work efficiency and effectiveness should undoubtedly be developed in the a gricultural sector. Traditional farmers can utilize technology to enhance their performance and achieve better and higher yields. Red chili peppers are one of the important agricultural commodities that need to be developed due to their high economic value. They are a national and regional flagship commodity and hold a significant position in the food menu as they are consumed daily by almost the entire population of Indonesia, albeit in small quantities. This plant can grow well in both lowland and highland areas, but its growth is better in lowland regions. The ideal air temperature for chili pepper growth is between 18-27°C, as temperatures below 16°C and above 32°C can hinder fertilization. As for soil moisture, chili pepper plants require 60% - 80%  humidity. Cultivating red chili peppers in limited land, either directly or in pots, can be a solution to address scarcity and meet family needs. Smart garden technology serves a purpose and provides benefits to farmers or plant owners, serving as a communication solution with plants.